Who Got the Brexit Blues? The Effect of Brexit on Subjective Wellbeing in the UK. (1st February 2019) - Powdthavee, Nattavudh; Plagnol, Anke C.; Frijters, Paul; Clark, Andrew E.
Abstract : We use the 2015–16 waves of the UK Household Longitudinal Study (Understanding Society) to look at subjective wellbeing around the time of the June 2016 EU membership Referendum in the UK (Brexit). We employ measures of both evaluative and affective wellbeing, namely life satisfaction and mental distress, respectively. We find that those reporting lower life satisfaction in 2015 were more likely to express a preference for leaving the EU in 2016, while mental distress was less predictive of pro‐Brexit attitudes. Post‐Referendum, those with Leave preferences enjoyed an increase in life satisfaction but there was no change in average life satisfaction in the overall sample. In contrast, the average level of mental distress increased in the sample post‐ Referendum, with no significant difference between those preferring to remain in or to leave the EU. We test the robustness of our results by considering a number of potential caveats, such as sample selection, unobserved individual fixed effects and the interval between interviews. Overall, our results suggest that levels of subjective wellbeing may be both a cause and a result of the 2016 Brexit vote.